Ending poverty as we know it : guaranteeing a right to a job at a living wage - Quigley, William P. (Temple University Press, 2003)
Across the United States tens of millions of people are working forty or more hours a week ... and living in poverty. This is surprising in a country where politicians promise that anyone who does their share, and works hard, will get ahead. InEnding Poverty As We Know It, William Quigley argues that it is time to make good on that promise by adding to the Constitution language that insures those who want to work can do so-and at a wage that enables them to afford reasonable shelter, clothing, and food. Author note: William P. Quigleyis the Janet Mary Riley Distinguished Professor of Law and Director of the Law Clinic and the Gillis Long Poverty Law Center at Loyola University, New Orleans. He has been an active public interest lawyer for over 20 years, and served as counsel for a wide range of public interest organizations on issues including public housing, voting rights, death penalty, living wage, civil liberties, civil disobedience, educational reform and constitutional rights. Quigley has litigated numerous cases with the NAACP Legal Defense and Educational Fund Inc., and served as General Counsel for the ACLU of Louisiana for 15 years. He has served as Chair of the Louisiana Advisory Committee to the U.S. Commission on Civil Rights and with many other local, state, and national legal and civil rights organizations. He has been counsel for ACORN and other community groups in the effort to enact a one dollar an hour raise in the minimum wage for every worker in New Orleans.